The Influence of Self-Efficacy on Understanding Arabic Syntax in Arabic Language Education Study Program Students, Jambi University Class - Putri, Azila Munawaroh; Iryani, Eva; Pratama, Firman Afrian (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
This research aims to analyze the influence of self-efficacy on understanding Arabic syntax among students of the Jambi University Arabic Language Education Study Program Class of 2022. This research was conducted at FKIP Jambi University in November 2023-March 2024. Research data was obtained by distributing questionnaires/ questionnaire and distributed test questions to students of the Jambi University Arabic Language Education Study Program Class of 2022. After obtaining the data, the data was analyzed using quantitative research with a correlational type of research. The results of the research show that there is an influence and relationship between the variable self-efficacy and the variable understanding Arabic syntax with a moderate degree of relationship and a positive form of relationship. Knowing that N = 38, the value of r table is at the 5% level or 0.05 = 0.320. As is known, data is said to be correlated if r count > r table and p value sig. < 0.05. It is known that the calculated r is 0.459 > ​​0.320 and the significance value is 0.004 < 0.05. Then, based on the calculation of the determinant coefficient, the magnitude of the contribution of self-efficacy and understanding of Arabic syntax is obtained based on the calculation of KD = r2 x 100%, then, (0.459)2 x 100% = 21.06% and the remaining 78.94% is influenced by other factors not included in this study. Based on the results of these data calculations, Ha is accepted and Ho is rejected, so that a positive and significant influence is obtained between self-efficacy and the variable understanding of Arabic syntax.